The Synonymy of the Story and the Message in Abdullah Hussain’s Novel Masuk ke dalam Cahaya - Tahir, National University of Malaysia (UKM), Ungku Maimunah Mohd (Asiatic: IIUM Journal of English Language and Literature, 2013)
When Abdullah Hussain’s novel Masuk ke dalam Cahaya, which won a consolation prize in an Islamic novel-writing competition in 1983, first met its reading public in the same year, there was no home-grown analytical framework, one dedicated to the Islamic worldview, to evaluate its literary merit and worthiness as an Islamic novel. But now there is the recently and locally-produced Persuratan Baru which, in consonant with Islamic precepts, prioritises true knowledge, and distinguishes between discourse and story, the former to articulate knowledge and the latter to develop and disseminate the knowledge so articulated. It also introduces, in ascending order of literary worthiness, the three categories of persuratan, sastera and picisan with persuratan and picisan occupying the highest and lowest strata respectively. With Persuratan Baru as its critical tool, the article examines the novel’s objective, and the extent to and manner in which the objective realised has been put to the service of disseminating true knowledge. The article argues that Masuk ke dalam Cahaya dismisses discourse as irrelevant, and presents the story and the message or knowledge as synonymous entities. In so doing, the novel prevails as a work of sastera for which story-making and the story serve as its main literary preoccupation.